2013
DOI: 10.5935/abc.20130203
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Impact of Thoracic Aortic Disease in São Paulo State from 1998 to 2007

Abstract: BackgroundThe epidemiological characteristics of thoracic aortic diseases (TAD) in the State of São Paulo and in Brazil, as well as their impact on the survival of these patients have yet to be analyzed.ObjectivesTo evaluate the mortality impact of TAD and characterize it epidemiologically.MethodsRetrospective analysis of data from the public health system for the TAD registry codes of hospitalizations, procedures and deaths, from the International Code of Diseases (ICD-10), registered at the Ministry of Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
4
1
2
Order By: Relevance
“…However, these authors also found that there is a lack of information regarding the incidence and prevalence of TAD disease, whose mortality rate is high. Moreover, they noticed that patients with TAD are extremely difficult to manage, since local centers are often unable to effectively treat these patients, the referral of affected patients to centers specializing in TAD treatment is inefficient and the results of treatment provided by the centers to which patients are referred are often suboptimal 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these authors also found that there is a lack of information regarding the incidence and prevalence of TAD disease, whose mortality rate is high. Moreover, they noticed that patients with TAD are extremely difficult to manage, since local centers are often unable to effectively treat these patients, the referral of affected patients to centers specializing in TAD treatment is inefficient and the results of treatment provided by the centers to which patients are referred are often suboptimal 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In our midst, we still have little knowledge on the impact of this disease in the general population. It has been observed that its mortality in the state of São Paulo is still very high due to either the shortcomings and inefficiency of our health system in identifying, screening, and treating these patients or the inadequate results obtained with hospitalized patients receiving drug treatment or even those who had undergone a surgical procedure (despite results being substantially better when these patients underwent surgery) [ 7 ] .…”
Section: Introductionmentioning
confidence: 99%
“…A first step has been taken. In the state of São Paulo, even though a significant increase has been observed in the number of diagnostics, hospitalizations, and procedures during the period of the study [ 7 ] , there is a lot to be done in order to improve the results of these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Os dados da literatura determinam diferentes valores na prevalência do AAA devido às características clínicas de cada amostra e região. No Brasil um estudo retrospectivo feito de 1998 a 2007 com dados do registro de internações e procedimentos do Sistema Único de Saúde, revelou que o AAA e os aneurismas ocupam a 30º causa mais frequente de óbito na população do Estado de São Paulo, sendo 3.539 óbitos de homens devido à dissecação da aorta e 1.383 óbitos referentes à ruptura do AAA (3). A prevalência do AAA é 4% a 8% em homens e em mulheres 0,5% -1,5%, variando de acordo com raça, idade, história familiar, localização geográfica e consumo de cigarro (4).…”
Section: Introductionunclassified
“…Os fatores de risco mais frequentes associados à AAA neste estudo foram: gênero masculino, tabagismo, antecedente de AAA e portadores de doença arterial oclusiva periférica, insuficiência coronariana e doença pulmonar obstrutiva crônica (5). Nos Estados Unidos da América (EUA), a doença é 13ª causa de óbitos sendo responsável por 30.000 óbitos por ano, principalmente em indivíduos com mais de 60 anos (1)(2)(3)(4)(5)(6).…”
Section: Introductionunclassified